SOCIOPOLITICAL VIOLENCE AGAINST SOCIAL LEADERS AND DEFENDERS OF HUMAN RIGHTS IN THE POST-CONFLICT: DIFFICULTIES AND CHALLENGES FOR THE IMPLEMENTATION OF A STABLE AND DURABLE PEACE IN COLOMBIA - Nocua Caro, Diana (2019)
The present article addresses the reflection on the difficulties and challenges that will surge in the construction of territorial peace in Colombia, in view of the growing socio-political violence against social leaders and human rights defenders, in the period after the signing of the Peace Treaty between FARC and the government of Juan Manuel Santos. For this, some of the factors that account for the systematic nature of the commission of these events are addressed, from the analysis of the dynamics of the local powers that contribute to crime and the violation of the rights of those who perform the exercise of defense of these; to subsequently reflect on the growing political and social polarization that promotes, through incitement to hatred and persecution against political opponents, the use of violence and the permanence of institutional and irregular practices linked to the doctrine of the "internal enemy".